Effect of watering frequencies and rehydration on body weight, feed and nutrient intake of indigenous sheep - K N WADHWANI, M SAHANA, R J MODI, M M TRIVEDI (Indian Journal of Animal Production and Management, 2020)
The present experiment was conducted with the objective to study the effect of watering frequencies andrehydration on body weight, feed and nutrient intake of indigenous sheep under intensive production systemduring hot humid season. Eighteen adult dry non pregnant farm born Patanwadi and Marwari female (25-35kg) sheep were divided randomly on body weight basis in three treatment groups viz., T1: Control (wateringthrice in a day), T2: (12 hrs. watering interval - watering twice in a day), T3: (24 hrs. watering interval -watering once in a day).The body weight (kg), DMI (g/d and g/kg W0.75), DCPI (kg/100 kg BW and g/kgW0.75) and TDNI (g/d) of experimental animals were significantly (P < 0.05) influenced by different wateringfrequencies, whereas in rehydration phase body weight, feed and nutrient intake was non-significant. Theresults indicated that the adult sheep should be given ad libitum water at least twice a day at the intervalof 12 hrs. in hot humid season to sustain body weight, DMI (g/d and g/kg W0.75) and TDNI (g/d).